THE GAME OF SURFING ON THE IMAGINARY OF SURFER (Fiep Bulletin - online, 2015)
This article had the purpose of analyzing the surfing practice taking into account the perspective of the game. A half-structuralized interview was used on it and it was identified the imaginary of surfers and their relationship with nature, looking for answers revealed during its practice as well as before and after its accomplishment. The surfer enters the game in this contact with nature, observing it, when connecting to the sea searching for the wave and contemplating it, always looking for harmony rather than confronting it.
Keywords: game; imaginary; surf.